2022
DOI: 10.3389/fsufs.2022.979252
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carotenoids double-encapsulated and incorporate in functional stirred yogurt

Abstract: Carrot industry processing outputs 50% waste from raw materials; this waste contains polyphenols and carotenoids, which are a significant natural source of pro-vitamin A. Also, yogurt's high consumption globally allows for designing a new functional product. So the goal is to enhance the functionality of fortified stirred yogurt by incorporating carotenoid beads. The carotenoids were extracted from carrot waste using ultrasonication. Then nanoemulsion carotenoids incorporating with alginate to produce beads by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Other researchers, such as Atwaa et al (2022), have reported that AO activity decreases significantly in all fortified yogurt treated with fennel extract during storage. Similarly, Soliman and Nasser (2022) found that AO activity reduced significantly in stirred yogurt samples with the an increase in the storage period. Lin et al ( 2020) reported that the AO activity of Momordica charantia and Momordica charantia var.…”
Section: Total Phenolic Content and Antioxidant Activitymentioning
confidence: 80%
See 1 more Smart Citation
“…Other researchers, such as Atwaa et al (2022), have reported that AO activity decreases significantly in all fortified yogurt treated with fennel extract during storage. Similarly, Soliman and Nasser (2022) found that AO activity reduced significantly in stirred yogurt samples with the an increase in the storage period. Lin et al ( 2020) reported that the AO activity of Momordica charantia and Momordica charantia var.…”
Section: Total Phenolic Content and Antioxidant Activitymentioning
confidence: 80%
“…Table 1 indicates that AO activity decreased during storage in all samples, but the treated samples had higher AO activity compared to the control sample after 21 days of storage (p < 0.05). The higher antioxidant activity detected using DPPH in the treated samples could be ascribed to the presence of phenolic and flavonoid components or secondary or subsidiary metabolites produced from them with AO activity that persisted over 21 days of storage) Soliman and Nasser, 2022). Other researchers, such as Atwaa et al (2022), have reported that AO activity decreases significantly in all fortified yogurt treated with fennel extract during storage.…”
Section: Total Phenolic Content and Antioxidant Activitymentioning
confidence: 87%
“…Approximately 0.097 ± 0.007 mg/g of lutein and 49.75 ± 3.15 mg/g of β-carotene were present in carrot waste extract, respectively. On the other hand, according to 28 , carrot pomace extract by sonication contains around 44.75 mg of β-carotene.…”
Section: Resultsmentioning
confidence: 99%